Stress-strain state of rectangular shallow shells of variable thickness under various boundary conditions - Grigorenko, A.Ya.; Yaremchenko, N.P.; Yaremchenko, S. N. (Reports of the National Academy of Sciences of Ukraine, 2016)
The stress-strain state of a shallow rectangular orthotropic shell with variable thickness in two coordinate directions at different boundary conditions on the edges in refined formulation is studied. The numerical-analytical approach based on the spline approximation and the method of discrete orthogonalization is used to solve two-dimensional boundary-value problems.